Applicability, Safety, and Efficiency of Salpingectomy versus Electrocoagulation and Laparoscopic Tubal Section in Ambulatory - Pereira, Joana Margarida Araújo; Trocado, Vera Filipa Batista; Gomes, Sandra Marina Sousa; Carlos-Alves, Mariana; Carvalho, Agostinho; Pinheiro, Paula Alexandra (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2022)
Objective Female sterilization is a surgical procedure that aims women to permanently stop the use of conception. The benefits, risks and cost-effectiveness are important issues. The purpose of this study was comparing the applicability, complications and efficacy of salpingectomy versus electrocoagulation and tubal occlusion by laparoscopy in the Ambulatory Surgery Unit.Methods We performed a retrospective and observational study that included women undergoing laparoscopic sterilization procedures at our Ambulatory Surgery Unit, during three years. Statistical analysis was performed using SPSS, applying the Fisher exact test, the Mann-Whitney test, and Linear Regression.Results Two hundred and twenty-one laparoscopic surgical procedures were performed, including 79 (35.7%) bilateral total salpingectomies and 142 (64.3%) electrocoagulation and bilateral tubal occlusion procedures. The majority of the procedures were performed by a resident (n = 162; 73.3%), with 40% (n = 33) of salpingectomies. The surgical time, independently the type of surgeon, was significantly shorter in the tubal occlusion (42.2 vs. 52.7 min, p < 0.001). Safety and efficacy endpoints were not significantly different between the two groups, with a case of pregnancy in tubal occlusion group.Conclusion Salpingectomy is a safe and effective alternative comparing with electrocoagulation and tubal occlusion.
Keywords: female; sterilization; salpingectomy; laparoscopic surgery; ovarian cancer